Hubungan Status Gizi dengan Tingkat Produktivitas Pekerja Wanita di PT. Idec Abadi Wood Industries Tarakan - Risaldi Risaldi; Ratih Wirapuspita; Iriyani Kamarudin (Jurnal Kesehatan, 2017)
Factors that affect worker producktivity is the intake level of nutrient of worker who can be seen from their nutritional status. The need for workers nutrition must be in accordance with the job. A worker with a good nutritional state will have a better working capacity and endurance, on the other hand a worker with a poor nutritional state will accelerate exhaustion and this can disrupt productivity. This study aims to know the correlation of nutritional status that consists of body mass index, energi intake, protein intake,  and intake of iron to the productivity of female workers in PT. Idec Abadi Wood Industries. This study uses cross sectional study design. The sample in this study was a female worker at the wholesale totaling 50 people, by measured the body mass index (BMI) and recall 24 hours. Data analysis technique used is multiple linier regression. Result from the study showed an association between nutrional status (BMI) and productivity (0,001 < 0,05), energy intake with productivity (0.008 < 0,05), intake of iron with productivity (0.045 < 0.05). And there was no significant association between protein intake and productivity (0,243 < 0,05). Companies were advised to make a special program for the monitoring process and the adequacy of nutrient intake of workers. The company needs to add medical personel especially in the field of nutrition. Dissemination of information through sosialization, posters or leflets on the pattern of balanced nutrition for workers